Adaptive Planning for Resilient Coastal Waterfronts - van Veelen, Peter Christiaan (A+BE | Architecture and the Built Environment, 2016)
Many delta and coastal cities worldwide face increasing flood risk due to changing climate conditions and sea level rise. The question is how to develop measures and strategies for existing urban coastal areas that can anticipate these slowly changing conditions, such as gradually increasing sea levels and extreme river discharges. There is growing recognition that the increasing vulnerability of urbanised delta and coastal cities is strongly related to urbanisation, changing socio-economic conditions and human-induced land subsidence. Consequently, in response to climate change, it is likely to be most effective to adapt existing urban environments and urban assets, and promote flood sensitive behaviour in combination with prevention based approaches, aiming to improve the whole capacity of the urban system to deal with changing and more extreme conditions in the future. This approach is known as the resilience approach. Although there is much focus on resilience in research and practice, it still lacks knowledge on the effectiveness of measures, and increasing coastal flood resilience is mostly understood in terms of risk reduction and not yet as an opportunity for change and creating liveability. In addition, it lacks knowledge on processes of urban development, management and change at the neighbourhood level as an important condition for creating coastal flood risk resilience and to create added value. The main research question of this thesis is therefore twofold: “how can we adapt existing coastal urban waterfront areas to changing climatic circumstances and how can we take this adaptation process as an opportunity for creating added value?” When adapting urban environments three challenges can be identified. First of all, it is necessary to understand under what conditions coastal urban systems become less resilient and adaptation is needed, and what (combinations) of measures are most effective to improve resilience. Secondly, key to the successful adaptation of urban environments is effectively using moments of change in urban development and management as windows of opportunity for low-cost adaptation, and to yield additional benefits. This requires a better understanding of the opportunities to spatially and in a timely manner, synchronise adaptation measures with investments in urban development, urban management and infrastructure maintenance projects at the neighbourhood level. Changes can be both incremental, for example building renovation cycles as an opportunity for retrofitting flood resilience measures into buildings, or can be transformative, for example by using urban redevelopment projects that create new options for adaptation. Finally, a major challenge of adapting existing urban environments to the effects of climate change is that it requires anticipating long-term trends and changes that easily exceed periods of 50 to 100 years. This brings large uncertainties into the design and planning process. When facing deep uncertainty it is necessary to improve flexibility. Improving flexibility can be either tactical-operational (designed) or strategic (planned). Designed flexibility can be achieved by developing design that anticipates, or can adapt according to future conditions or functional requirements. This can be achieved by incorporating modifications in the design, through preserving space, by over-dimensioning critical elements or by built-in redundancies. On a strategic level, flexibility can be achieved by developing sequences of adaptation options that keep options open in anticipation of future conditions. Sequences of adaptation options (pathways) that are reversible and offer multiple options to adapt should be favoured over irreversible and non-flexible paths. To answer the research question, this research applies a resilience based planning method (the Adaptive Pathways Method, or APM) to develop and assess adaptation pathways at the level of neighbourhood development in two flood prone waterfront cases in Rotterdam. APM is a structured, iterative approach based on defining the conditions under which policy objectives are no longer attainable and adaptation is required, and the assessment of sequences of adaptation actions. It enables policy makers to explore and develop adaptive strategies The case study research in two flood prone urbanised areas in Rotterdam showed that Rotterdam’s land elevation policy for new building plots is expensive and offers no solution to reduce the flood risk of existing homes and businesses in the area. In this study, two alternative solutions (water robust and keeping water out) were developed and tested for spatial integration, (cost) effectiveness and opportunities for creating added value. The Feijenoord case shows that a district-wide flood protection strategy provides the most beneficial solution and opens up opportunities for capitalising on investments in waterfront development and improvements of the urban realm. The Noordereiland case shows a more diverse portfolio of adaptation responses, although there are only a few combinations of adaptation responses that are complementary to deal with change in the long run. A potential adaptation strategy for the Noordereiland is based on sequencing property level protection (wet-proofing and dry-proofing adaptation measures), followed by the development of a permanent or temporary floodwall strategy. However, this strategy offers few opportunities to link with spatial dynamics and to create added value. Based on case study research, this research concludes that the APM is an effective tool to evaluate and select appropriate adaptation measures. In particular, the value of this method is that it helps to bridge the gap between highly uncertain long-term climate change effects and the short-term decision making horizons of urban planning and development. Additionally, the method helps to better grasp the timing of adaptation and develop a wide portfolio of adaptation actions, which opens up opportunities to couple adaptation measures with other planned investments, or to anticipate by developing urban design that allows for easier adaptation in the future. Both cases underline the fact that strategies to enhance the resilience of urban waterfronts must be based on a detailed assessment of local vulnerabilities, and should select sitespecific adaptation measures leading to a tailor-made portfolio of solutions. An important element of adaptive planning is the assumption that a transfer between, or sequencing alternative interventions (and thus developing alternative pathways) is straightforward. However, in reality there is no smooth transfer between alternatives. Both cases clearly show that a change of strategy, for example from property-level to a district-wide solution, is accompanied with ‘transfer costs’ that creates an economic lock-in and is constrained by legal, financial and institutional barriers. For example, every investment to reduce a household’s sensitivity to flooding reduces the overall flood risks of the larger area and hence the benefits accruing to a wider floodwall option, making a ‘transfer’ to a district-level solution less feasible from an economic point of view. In addition, the potential loss of investments for individual homeowners caused by a change of strategy could lead to societal and political resistance to change. Overcoming the economic and political path dependencies is a major challenge and it unfortunately often needs a disaster to change the course of an adaptation path. Possibly, co-benefits and added value arising from flood protection investments (e.g. increase in real estate value) may have a positive effect on reducing the transfer costs, although the effects strongly depend on site conditions. In view of the above, it is necessary to decide early in the adaptation process on the long-term preferred strategy and to support this strategy with short-cycle, low cost incremental interventions aimed at “buying time” to increase the opportunities for creating district-wide protection at low costs. In addition to this, there is also a second, more fundamental shortcoming of the method. Although the APM is adaptive, in the sense that it allows for uncertainties to be resolved in time, the method ignores the dynamic aspect of urban development and new opportunities for adaptation that might arise from it. For example, a redesign of industrial waterfronts to residential functions creates new financial and spatial opportunities for creating integrated flood protection at relatively low costs. Research by Design is an important tool to explore these new opportunities. A more effective approach is to focus on interventions in the economic and institutional processes of urban development and changes that create new opportunities for adaptation. In the second part of this research an urban dynamics based adaptation method is introduced that focuses on identifying the following: adaptation intervention points, which are defined as the actual moments of change that potentially may be used for adaptation; adaptation transitions that are defined as changes in legal, institutional and financial structures that are needed to improve or unlock the full potential of adaptation intervention points; and adaptation transformations that are fundamental changes in urban form, policies, institutional arrangements and norms that could create new adaptation opportunities. The method follows three basic steps: (1) assessing the spatial and timely synchronisation of adaptation measures with planned urban development projects and public and private infrastructure maintenance investments; (2) assessing the institutional and financial barriers to be removed in order to mainstream climate adaptation measures in these urban development processes, and (3) assessing what opportunities derived from urban development are able to ‘break through’ the path dependencies that lock-in more sustainable adaptive paths. The method is based on mapping all planned spatial investments in brownfield development, urban renovation, and maintenance projects of public and private infrastructure and assets and by assessing the effectiveness of prevailing policies. Using design research, new opportunities for adaptation are explored and assessed. The urban dynamics based adaptation pathways method is tested at two waterfront areas in Rotterdam (Feijenoord) and New York (Red Hook). Both cases show that identifying intervention opportunities and potential transitional interventions is helpful in selecting and assessing adaptive pathways. Moreover, it helps to identify legal or financial arrangements that are needed to unlock the potential of adaptation paths. One of the key findings of the case study research is that in high density urban conditions there is limited potential to build resilience from household redevelopment or renovation, even when new complementary policies and regulative instruments that support buildinglevel resilience would be developed. District-wide flood protection is effective in terms of flood risk, but requires large-scale transformations of the waterfront zone to seize opportunities to develop integrated protection at low costs. This strategy, however, needs new governance structures and financial arrangements to redistribute costs and benefits fairly among stakeholders.